The Integration of Higher Order Thinking Skills by Certified English Teachers in Senior High School - Arifah, Fildzah; Muthalib, Kismullah Abdul (Institut Agama Islam Negeri (IAIN) Curup, 2025)
Examining the challenges in implementing Higher-Order Thinking Skills (HOTS) among certified English teachers offers valuable insights into teachers’ professional competences and the quality of the instructional process. This process involves the development of lesson and assessment plans, in which HOTS is a key component aligned with the demands of 21st-century education. This study aimed to explore the teaching practices and challenges encountered by three certified English teachers at Babul Maghfirah High School in Aceh in their efforts to integrate HOTS into classroom instruction. The research specifically focused on evaluating teaching activities based on established HOTS-based learning criteria and identifying the obstacles that hindered effective implementation. Data were collected using checklists, observation guides, and semi-structured interviews. The participants in this study were three certified English teachers, and the primary objects of analysis were their lesson plans, assessments, and teaching practices. This study adopted a qualitative descriptive approach within a case study framework. Data collection was conducted through classroom observations and in-depth interviews. The findings revealed that the instructional practices did not fully align with the principles of HOTS-based learning. Teacher-centered approaches remained dominant, the integration of 4C skills (critical thinking, communication, collaboration, and creativity) was incomplete, and conventional teaching methods were still prevalent. Furthermore, the study identified several contributing factors to these shortcomings, including limited teacher understanding of HOTS, insufficient school facilities, and students’ difficulties in comprehending lesson content. Therefore, the incomplete implementation of HOTS by certified English teachers reflected a broader issue of unmet criteria in HOTS-based instructional design.